Subscription Page (The Review of Asset Pricing Studies, 2013)
Journal Article Subscription Page Get access The Review of Asset Pricing Studies, Volume 3, Issue 2, December 2013, Page i3, https://doi.org/10.1093/rapstu/ras023 Published: 11 November 2013